Respuesta :

Answer:


Step-by-step explanation:

1.  [tex]4(2x^{2}+3y^{2})^{2}[/tex]

=[tex]4(4x^{4}+9y^{4}+12x^{2}y^{2})[/tex]

= [tex]16x^{4}+36y^{4}+48x^{2}y^{2}[/tex]

2.  [tex]4(2x^{2}+3y^{2})(2x^{2}-3y^{2})[/tex]

=[tex]4((2x^{2})^{2}-(3y^{2})^{2})[/tex]

=[tex]4(4x^{4}-9y^{4})[/tex]

= [tex]16x^{4}-36y^{4}[/tex]

3.  [tex](4x-5)(16x^{2}+20x+25)[/tex]

=[tex]64x^{3}-80x^{2}+80x^{2}-100x+100x-125[/tex]

= [tex]64x^{3}-125[/tex]

Answer:

4(2x^2+3y^2)^2 = 16x^4 + 48x^2y^2 + 36y^4

(4x-5)(16x^2 + 20x + 25) = 64x^3 - 125

4 ( 2x^2 + 3y^2)(2x^2 - 3y^2) = 16x^4 -36y^4

Step-by-step explanation:

ACCESS MORE